„Je to jiné, než jak to vypadá v médiích.“: Nespokojenost s politikou a perspektiva poslanců a poslankyň - Kawulok, Josef (Lidé města, 2024)
To understand the causes of political dissatisfaction is of great importance in the Czech Republic. Unlike in traditional democracies, it is satisfaction or dissatisfaction with politics that affects the degree of legitimacy of its democratic system. Existing knowledge offers several possible explanations of this phenomenon. The most universal among them is the public assessment of the quality of various aspects of politics and politicians. Following this, this article argues that these findings lack complexity, because they do not reflect the perspective of politicians. The article is based on the assumption that the political (dis)satisfaction and legitimacy of democracy are created in a cyclical process of mutual interaction between the public and politics. So, if the public formulates certain policy change requirements, politicians can potentially respond to them. The main problem is that they do not do that and existing research has no explanation for this. Based on an analysis of interviews with Czech MPs, this article argues that politicians do not respond adequately to public demands because their experience with politics is organised in a specific way. The public organises its experience with politics differently, because media news are the main source of its information about politics. In the form of the organisation of political experience of MPs, it is essential that they perceive political phenomena in a broader context, that they differentiate the degree of importance and relevance of their own experience with them in a specific way, and that they also transform the meaning of some of their aspects. In their perspective, it is, therefore, not the existing form of politics nor even the politicians themselves that should change, it is the public that should change.